Functional evaluation of two corneal endothelial cell-based therapies : tissue-engineered construct and cell injection - Peh, Gary S. L. (2019)
Restoration of vision due to corneal blindness from corneal endothelial dysfunction can be achieved via a corneal transplantation. However, global shortage of donor tissues has driven the development cell-based therapeutics. With the capacity to propagate regulatory compliant human corneal endothelial cells (CEnCs), this study evaluated the functionality of propagated CEnCs delivered via tissue-engineered endothelial keratoplasty (TE-EK) or corneal endothelial cell injection (CE-CI) within a rabbit model of bullous keratopathy. For animals with TE-EK grafts, central corneal thickness (CCT) increased to >1000 μm post-operatively. Gradual thinning with improvements in corneal clarity was observed from week 1. CCT at week 3 was 484.3 ± 73.7 μm. In rabbits with CE-CI, corneal clarity was maintained throughout, and CCT at week 3 was 582.5 ± 171.5 μm. Control corneas remained significantly edematous throughout the study period compared to their respective experimental groups (p < 0.05). Characterization of excised corneas showed a monolayer with heterogeneously shaped CEnCs in both TE-EK and CE-CI groups. Immunohistochemistry demonstrated reactivity to anti-human specific nuclei antibody attributing corneal recovery to the functional human CEnCs. This study showed that regulatory compliant cell-based therapy for corneal endothelial dysfunction can be delivered by both TE-EK and CE-CI, and holds great promise as an alternative to traditional corneal transplantation.